Assessing The Impact of Hygiene Practices on Women’s Health: A Public Health Case Study - R, Annapurna; M. Kudari, Siddalingesh (Journal of Neonatal Surgery, 2025)
Background: Effective hygiene practices are essential for maintaining women's health, preventing infections, and enhancing overall quality of life. Poor hygiene, particularly menstrual hygiene, poses significant health risks and complications. Objective: To evaluate the impact of personal and menstrual hygiene practices on health outcomes in an individual female, highlighting the importance of public health education. Methods: A detailed observational single-case study was conducted on a 30-year-old woman experiencing recurrent urinary and reproductive tract infections. Data were collected through structured interviews, observation of personal hygiene behaviors, and clinical examinations over a six-month period. Results: Following the implementation of improved hygiene practices, including enhanced menstrual hygiene management, the subject showed marked reductions in infection frequency, decreased discomfort, and significant improvement in overall health and quality of life. Conclusion: Adherence to proper hygiene practices considerably improves women's health outcomes. Public health strategies should emphasize targeted hygiene education to promote better health among women.